Genetic dissection of cold stress tolerance and yield potential under cold stress in nested synthetic wheat (Triticum aestivum L.) introgression libraries using multi-locus genome-wide association and haplotype analysis - Mukesh Rathore; Nikita Aggarwal; Abhishek Pandey; Satinder Kaur; Mohd. Ashraf Bhat; Sundeep Kumar; Mohd Anwar Khan; Parvaze Ahmad Sofi; Reyazul Rouf Mir (Functional & Integrative Genomics, 2026)
Cold stress is a major abiotic constraint to wheat production in temperate regions, particularly in the Kashmir Valley of north-western Himalayas, India, where prolonged low temperatures delay growth, reduce yield, and disrupt the rice–wheat cropping system. To address this challenge, we evaluated a panel of 340 nested synthetic hexaploid wheat introgression lines, developed by introgressing allelic diversity from Aegilops tauschii and Triticum durum into bread wheat. The panel was phenotyped for cold stress tolerance, electrolyte leakage index, and yield-related traits across three temperate environments and genotyped using the 35 K Axiom® Wheat Breeder’s Array. Genome-wide association study using FarmCPU and BLINK models identified 152 stable marker–trait associations (MTAs), with − log₁₀(P) values ranging from 3.00–14.64. Several stable MTAs surpassed the Bonferroni-adjusted significance threshold and were designated as high-confidence loci. A number of stable MTAs co-localized with previously reported genomic regions, whereas others represent potentially novel loci. Multiple pleiotropic loci were detected, indicating potential for simultaneous improvement of multiple traits. Haplotype analysis identified 32 major LD blocks significantly associated with target traits, with favorable haplotypes conferring enhanced stress tolerance and productivity. Several putative candidate genes were identified within chromosome-specific LD intervals of high-confidence MTAs. Literature mining, in silico expression profiling and network analyses further supported their functional relevance in cold stress adaptation and yield regulation. The identified genomic regions, haplotypes, and candidate genes provide valuable resources for marker-assisted and haplotype-based breeding to develop cold-tolerant, high-yielding wheat cultivars suited to temperate regions, thereby supporting the sustainability of rice–wheat cropping systems.

Integrated genome-wide association study (GWAS) and metabolomics identify genetic and metabolic drivers of stripe rust resistance in wheat from the Western Himalayas - Farkhandah Jan; M. Parthiban; Sofora Jan; Anjan Kumar Pradhan; Sundeep Kumar; Safoora Shafi; Mahpara Bashir; Divya Sharma; Naeela Qureshi; Manish Kumar Vishwakarma; Sarabjit Kaur; Jaspal Kaur; et al. (Functional & Integrative Genomics, 2026)

Bioactivity profiling of endophytic fungi isolated from Albizia lebbeck: Antimicrobial, antioxidant, and cytotoxic evaluations - Nisha Sharma; Tenzen Yodun; Arem Qayum; Shashank K. Singh; Umesh Goutam; Sundeep Jaglan (Brazilian Journal of Microbiology, 2026)

Genome wide association studies and expression analyses identify candidate genes for spot blotch resistance in bread wheat - G. Mahendra Singh; Uttam Kumar; Bhagya Shree Acharya; Pradeep Bhati; Manish Vishwakarma; Dinesh Kumar Saini; Sundeep Kumar; Vinod K. Mishra; Arun K. Joshi; Sandeep Sharma (Theoretical and Applied Genetics, 2026)

Identification and Characterisation of Super Susceptible Bread Wheat (Triticum aestivum L.) Landraces against Leaf Rust Pathogen (Puccinia triticina Eriks.) - Naman Raj; Ujjwal Kapoor; Ramesh Bhurta; Vrinda Batra; Subhash Bijarania; Niharika Mallick; M. G. Mallikarjuna; Vaibhav Kumar Singh; Atul Kumar; Om Prakash Gangwar; Pramod Prasad; Subhash Chander Bhardwaj; et al. (Indian Journal of Genetics and Plant Breeding, 2026)

LC-MS/MS-based discovery of new cytochalasin from fungus Rosellinia sanctae-cruciana - Nisha Sharma; Poonam Choudhary; Priya Kumari; Mohd Murtaza; Vidushi Abrol; Chetan Kumar; Rohit Singh; Sundeep Jaglan; Manoj Kushwaha (Natural Product Research, 2026)

Multi-criteria optimization of closed-loop hydronic pavement systems in urban heat island mitigation: Balancing performance and cost - Sundeep Inti; Srinivasan Arumugam; Sumeet J. Paramaj (Urban Climate, 2026)

Designing Nanocomposites of Conjugated Copolymers for the Removal of Bacterial Contamination from Polluted Water - Sundeep Kumar Dhawan; Surbhi Kohli; Ridham Dhawan; Vikas Garg; Hema Bhandari; Haritma Chopra; Badira M. Alshehri; N. S. Abd-El-Gawaad (Water, Air, & Soil Pollution, 2026)

Redefining coastal and marine boundaries through a 50-NM functional threshold for integrated ocean governance - P. Ragavan; R. Ramesh; Sundeep; K. Kathiresan; P. M. Mohan (Hydrobiologia, 2026)

Harnessing artificial intelligence in plant breeding: innovations in digital phenotyping and breeding methodologies - Nikita Aggarwal; Mukesh Rathore; Farkhandah Jan; Divya Sharma; Sundeep Kumar; Mahendar Thudi; Abdulqader Jighly; Rajeev K. Varshney; Reyazul Rouf Mir (Theoretical and Applied Genetics, 2026)
Agriculture plays a crucial role in the development of countries whose economies rely heavily on food production. In the face of climate change and growing global population, plant breeders are challenged to adopt more efficient crop improvement strategies. The advances in artificial intelligence (AI), particularly in large-scale data integration, analysis, and pattern recognition, have revolutionized several scientific disciplines, including plant breeding. In this review, we provide a comprehensive survey of the potential of AI tools in plant breeding with four key objectives: (i) revolutionizing high-throughput phenotyping, (ii) exploring AI-driven breeding methodologies beyond traditional approaches, (iii) optimizing breeding pipelines through improved modelling of genotype × environment × management interactions, and (iv) highlighting the limitations of AI in plant breeding and future directions. Case studies published during the past two decades illustrate successful implementations of AI-powered phenotyping and breeding frameworks for major traits across diverse crop species. Furthermore, AI tools show great promise in refining crop traits at the molecular level by increasing the accuracy and precision of emerging fields including gene editing and genomic selection. We emphasize the importance of interdisciplinary collaboration to maximize the benefits of AI in plant breeding programs and to support the sustainable and food-secure future. This review bridges the gap between AI and agricultural applications, offering a roadmap for researchers, industry professionals, and policymakers to harness information fusion and computational models for advancing precision agriculture. It will serve as a valuable resource for future plant breeding, accelerating crop improvement from phenotyping to genomic selection and breeding decision support.

Temporal transcriptomic profiling identifies core regulators in cytokine-induced gut barrier disruption in differentiated Caco-2 cells - Hyo Shin Yoon; Shining Ma; Matt Kanke; Wan-Jung Wu; Uyen Hoang; Jessica A. Tan; Alex Wilks; Priyanka Patel; Sundeep Chandra; Xin Luo; Daniel Lu; Scott Martin; et al. (Inflammation Research, 2026)
Objective The intestinal epithelial barrier maintains gut homeostasis, and its disruption contributes to inflammatory diseases such as Inflammatory Bowel Diseases (IBD). Although barrier restoration is a promising therapeutic strategy, most current approaches target immune responses rather than epithelial function. Since barrier injury and repair progress through discrete phases, this study aimed to define time-resolved epithelial transcriptional programs and identify candidate regulatory nodes for barrier-focused therapeutic intervention. Methods Differentiated Caco-2 epithelial monolayers were used to model cytokine-induced barrier disruption and profiled by time-resolved bulk RNA-seq. Transcriptional dynamics and candidate regulators were identified using pairwise differential expression, likelihood-ratio testing, pathway enrichment, and upstream-regulator inference. Candidate nodes were tested by pharmacologic perturbation, and disease relevance was assessed by qPCR and histology in human IBD colon tissues. Results Time-resolved profiling revealed dynamic epithelial programs involving the Rho GTPase cycle, sirtuin signaling, non-canonical WNT signaling, and junction/EMT-associated pathways. Upstream-regulator inference highlighted JAK2, TNF, gasdermin D, and β-estradiol, and pharmacologic perturbation of these nodes mitigated cytokine-induced barrier loss. HNF4A emerged as a gut epithelial transcriptional hub regulating targets including SATB2 and SLC26A3. Notably, SLC26A3 was markedly reduced in IBD colon tissues. Conclusions This study provides a time-resolved epithelial framework and highlights therapeutic opportunities for barrier-focused interventions.

Shear Stress Initiates Endothelial-to-Mesenchymal Transition in Endocardial Endothelial Cells - Kathleen N. Brown; Hong Kim T. Phan; Tasneem Mustafa; Elysa Jui; Fariha N. Ahmad; Ravi K. Birla; Philippe Sucosky; Jennifer P. Connell; Sundeep G. Keswani; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2026)
Discrete subaortic stenosis (DSS) is a congenital heart disease in which a fibrotic membrane forms below the aortic valve; the underlying cellular mechanisms are currently unknown. Since an elevated pressure gradient in the left ventricular outflow tract (LVOT) is a distinguishing feature of DSS, it is hypothesized that the membrane formation is caused by elevated wall shear stress applied to the endocardial endothelial cells (EECs) that line the LVOT, triggering fibrosis. To correlate shear stress to an EEC fibrotic phenotype, we applied fluid shear stress to EECs at physiological and pathological shear rates using a cone-and-plate device, designed to recapitulate physiological wall shear stress in a controlled in vitro environment. Controlled shear stress regimes were applied to EECs to replicate the conditions observed in DSS patients. We found that elevated shear stress triggered EEC alignment as well as endothelial-to-mesenchymal transformation (EndMT) signaling pathways driven by upregulation of SNAI1 gene expression. The EECs were then treated with a small molecule inhibitor of Snail1 protein, CYD19, to attempt to attenuate EndMT signaling, and subsequently subjected to pathological shear stress. The Snail1 inhibitor did downregulate selected markers of EndMT signaling, although only transiently. Interestingly, the application of shear stress had a greater effect on the EEC gene and protein expression than did the Snail1 inhibition. This investigation of EEC response to shear stress reveals the pronounced and complex effect of this mechanical stimulation on the EEC phenotype. Further study should reveal the mechanisms that drive fibrosis and the formation of the DSS membrane.

A novel fiber interlaced liposomal delivery of ursolic acid: Development, structural characterization, in vitro and in vivo bioavailability studies - Joby Jacob; Vedashree M. Sharma; T.V. Valsaraj; Heggar Venkataramana Sudeep; Kuppam Sundeep; Karempudi Venkatakrishna; Shyamprasad Kodimule (Next Research, 2026)

Effective selection criteria for high-throughput wheat drought tolerance screening using integrated physiological and statistical approaches - Pravin pawar; Sudhir Navathe; K. J. Yashavanthakumar; Jyoti Kumari; Sundeep Kumar; P. S. Basavaraj; S. K. Singh; Gyanendra Pratap Singh; Manoj Oak (Plant Physiology Reports, 2026)

Echinomycin, a peptide antibiotic from a new bacterial source and its potential to tackle drug resistance in methicillin-resistant Staphylococcus aureus - Mohd Murtaza; Nitika Bhasin; Priya Kumari; Avleen Kour; Poonam Choudhary; Manoj Kushwaha; Sandeep Sharma; Sundeep Jaglan (Archives of Microbiology, 2026)

Neurocaf™, A green coffee bean extract containing eicosanoyl-5-hydroxytryptamide and chlorogenic acids enhances cognitive function and neuronal plasticity in a scopolamine-induced amnesia mouse model - Karempudi Venkatakrishna; Kuppam Sundeep; Amritha Raj; Thammatadhahalli Parameshwarappa Pr Kumara; Harakanahalli Basavegowda Lingaraju; Kodimule Shyamprasad; Heggar Venkataramana Sudeep (Metabolic Brain Disease, 2026)

Bioactive potential metabolites from gut associated fungal endofauna of Eisenia fetida - Mohd Hassan; Shamsun Nisa; Manoj Kushwaha; Suruchi Gupta; Sundeep Jaglan; Sanket K. Shukla; Ravail Singh (Biocatalysis and Agricultural Biotechnology, 2026)

Strategies to decipher silent biosynthetic gene clusters in actinomycetes - Mohd Murtaza; Puja Gupta; Poonam Choudhary; Mehnaza Manzoor; Sandeep Sharma; Sundeep Jaglan (Archives of Microbiology, 2026)

Adoption of mobile-based agricultural extension services: evidence from South India - Marija Cerjak; Marco Medici; Ivica Faletar; Jada Venkata Sundeep; Maurizio Canavari (Journal of Rural Studies, 2025)

Deciphering pathological and population dynamics in Tilletia indica of Karnal bunt of wheat - Sangale Smita; Malkhan Singh Gurjar; Tej Pratap Jitendra Kumar; Jitender Kumar; Poulami Basak; Natasha Kashyap; Rahul Patidar; Muthyala Mahendra; Sri Ananth Kurella; Kartiki Sharma; Sundeep Kumar; Mahender Singh Saharan (Indian Phytopathology, 2025)

Smart nano-fertilizers: a path to sustainable agriculture - Puja Gupta; Hena Dhar; Yudhishther Singh Bagal; Sundeep Jaglan (Environmental Geochemistry and Health, 2025)

Shear Stress Conditioning Promotes a Pro-Inflammatory Response in Porcine Endocardial Endothelial Cells - Pengfei Ji; Kathryn Jane Grande-Allen; Swathi Balaji; Ravi K. Birla; Sundeep G. Keswani (Annals of Biomedical Engineering, 2025)

Genetic variability and correlation studies based on diverse wheat panel for grain yield and related attributes under north-western Himalayan conditions - Anoushka Sharma; Vijay Rana; Daizy Basandrai; Sundeep Kumar; Nimit Kumar; Ankita Mohapatra; Naiya Sharma; Anish Dhiman; Akhilesh Sharma (Vegetos, 2025)

Comprehensive analysis of genomic loci associated with glaucousness in wheat (Triticum aestivum L.) through Genome-wide association study - Shiveta Sharma; Vikas Kumar Singh; Satish Kumar; Vivek Patel; Saksham Pundir; Ajay Kumar; Sundeep Kumar; Marion S. Röder; Shailendra Sharma (Physiology and Molecular Biology of Plants, 2025)

Plant Defense Hormones: Thermoregulation and Their Role in Plant Adaptive Immunity - Zahoor Ahmad Mir; Sajad Ali; Subaya Manzoor; Divya Sharma; Deepak Sharma; Anshika Tyagi; Ab Waheed Wani; Sundeep Kumar; Belay T. Ayele (Journal of Plant Growth Regulation, 2025)

Recent Trends in Electricity Generation from Lignocellulosic Biomass-Fueled Microbial Fuel Cells - Pardeep Kaur; Preeti Saini; Sundeep Kaur; Maulin P. Shah (Indian Journal of Microbiology, 2025)

Cardioprotective Foods: A Molecular Perspective on Pathways and Mechanisms - Ghulam Mehdi Dar; Amanpreet Kaur; Parameswar Sahu; Vishal Batra; Bhawna Mahajan; Mohammad Mahfuzul Haque; Sundeep Singh Saluja (Current Food Science and Technology Reports, 2025)

Extraction of geometric and transport parameters from the time constant of exocytosis transients measured by nanoscale electrodes - Sundeep Kapila; Pradeep R. Nair (European Biophysics Journal, 2025)

Metabolite profiling and bioactivity of fungal endofauna from Xiphinema nuragicum in the rhizosphere of Withania somnifera - Jyoti Chandan; Suruchi Gupta; Zabeer Ahmed; Shashank Kumar Singh; Puneet Kumar; Rupali Choudhary; Sundeep Jaglan; Yogesh Bharitkar; Gurleen Kour; Ekta Nehra; Ravail Singh (Environmental Science and Pollution Research, 2025)

Synthesis and Study of pH Independent L-Cysteine Capped Zirconium Oxide Quantum Dots as a Potential Bio-Imaging Probe Using HeLa Cells - Surya Pratap; Himanshu Meena; Shashi kant sharma; Vijay Kumar Sonkar; Sundeep Kumar; Horesh Kumar (Journal of Fluorescence, 2025)

Current Trends and Advances in Nanoplatforms-Based Imaging for Cancer Diagnosis - Kovuri Umadevi; Dola Sundeep; Alluru Raghavendra Vighnesh; Aroonima Misra; Alluru Gopala Krishna (Indian Journal of Microbiology, 2025)

Prevention is better than cure: immunocompromised people need COVID-19 prevention therapies now - Antonio Pagliuca; Sundeep Kaul; Carl S. Goodyear; Lennard Lee (Infectious Diseases, 2024)

Dissecting physiological traits for drought and heat tolerance in wheat - Sindhu Sareen; B. K. Meena; Ashok Sarial; Sundeep Kumar (Cereal Research Communications, 2024)

Development of Novel 3D Spheroids for Discrete Subaortic Stenosis - Sunita Brimmer; Pengfei Ji; Ravi K. Birla; Jeffrey S. Heinle; Jane K. Grande-Allen; Sundeep G. Keswani (Cardiovascular Engineering and Technology, 2024)

The potential of biochar incorporation into agricultural soils to promote sustainable agriculture: insights from soil health, crop productivity, greenhouse gas emission mitigation and feasibility perspectives—a critical review - Muhammad Saif Ullah; Raheleh Malekian; Gurjit S. Randhawa; Yuvraj Sing Gill; Sundeep Singh; Travis J. Esau; Qamar U. Zaman; Hassan Afzaal; Dao Lin Du; Aitazaz A. Farooque (Reviews in Environmental Science and Bio/Technology, 2024)

Exposure to traffic and greenspace, and associations with respiratory health in urban India - Sowmya Malamardi; Katrina Lambert; Sheetu Singh; Sundeep Salvi; Sushil K. Kabra; Meenu Singh; Shally Awasthi; Arvind Kumar Sharma; Sabir Mohammed; Thevaruparambil U. Sukumaran; Aloke G. Ghoshal; Nishtha Singh; et al. (Urban Climate, 2024)

Shear Stress Induces a Time-Dependent Inflammatory Response in Human Monocyte-Derived Macrophages - Elysa Jui; Griffin Kingsley; Hong Kim T. Phan; Kavya L. Singampalli; Ravi K. Birla; Jennifer P. Connell; Sundeep G. Keswani; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2024)

Precision Detection of Fungal Co-Infections for Enhanced COVID-19 Treatment Strategies Using FESEM Imaging - Kovuri Umadevi; Dola Sundeep; Eswaramoorthy K. Varadharaj; Chebbiyam Chandrasekhara Sastry; Arundhathi Shankaralingappa; Rajarikam Nagarjuna Chary; Alluru Raghavendra Vighnesh (Indian Journal of Microbiology, 2024)

Recent Development in Nanoparticle-Assisted Microbial Fuel Cell for Enhanced Reduction of Chromium - G. Vijay Samuel; Nibedita Dey; R. Govindarajan; Kuppusamy Sathishkumar; Muthusamy Govarthanan; J. Sakthidasan; J. Sandhya; Lakshmi Sundeep (Current Microbiology, 2024)

Identification of hub genes associated with stripe rust disease in wheat through integrative transcriptome and gene-based association study - Divya Chauhan; Dwijesh Chandra Mishra; Shikha Mittal; Sushma Rani; Jyotika Bhati; Sundeep Kumar; Subhash C. Bhardwaj; Monendra Grover; Neeraj Budhlakoti; Suphiya Khan (South African Journal of Botany, 2024)

Epigenetic modifiers as inducer of bioactive secondary metabolites in fungi - Vishal Sharma; Shivali Panjgotra; Nisha Sharma; Vidushi Abrol; Umesh Goutam; Sundeep Jaglan (Biotechnology Letters, 2024)

In-silico characterization of drought stress related WRKY2 transcription factor in wheat crop (Triticum aestivum L.): study of its physico-chemical properties and structural dynamics - Deepali Upadhyay; Neeraj Budhlakoti; Jyoti Kumari; Nidhee Chaudhary; Jasdeep Chatrath Padaria; Sindhu Sareen; Sundeep Kumar (Genetic Resources and Crop Evolution, 2024)

Non-Fourier Bioheat Transfer Analysis in Brain Tissue During Interstitial Laser Ablation: Analysis of Multiple Influential Factors - Sundeep Singh; Leonardo Bianchi; Sanzhar Korganbayev; Pouya Namakshenas; Roderick Melnik; Paola Saccomandi (Annals of Biomedical Engineering, 2024)
This work presents the dual-phase lag-based non-Fourier bioheat transfer model of brain tissue subjected to interstitial laser ablation. The finite element method has been utilized to predict the brain tissue's temperature distributions and ablation volumes. A sensitivity analysis has been conducted to quantify the effect of variations in the input laser power, treatment time, laser fiber diameter, laser wavelength, and non-Fourier phase lags. Notably, in this work, the temperature-dependent thermal properties of brain tissue have been considered. The developed model has been validated by comparing the temperature obtained from the numerical and ex vivo brain tissue during interstitial laser ablation. The ex vivo brain model has been further extended to in vivo settings by incorporating the blood perfusion effects. The results of the systematic analysis highlight the importance of considering temperature-dependent thermal properties of the brain tissue, non-Fourier behavior, and microvascular perfusion effects in the computational models for accurate predictions of the treatment outcomes during interstitial laser ablation, thereby minimizing the damage to surrounding healthy tissue. The developed model and parametric analysis reported in this study would assist in a more accurate and precise prediction of the temperature distribution, thus allowing to optimize the thermal dosage during laser therapy in the brain.

Biodiversity and Bioactive Potential of Actinomycetes from Unexplored High Altitude Regions of Kargil, India - Mohd Murtaza; Vidushi Abrol; Ekta Nehra; Poonam Choudhary; Shashank K. Singh; Sundeep Jaglan (Indian Journal of Microbiology, 2024)

A Rapid 3-Day Excipient Screening Methodology and its Application in Identifying Chemical Stabilizers for Solid Formulations with Mixed Mechanisms of Degradation - Amol S. Matharu; Sundeep S. Dhareshwar; Yu Cao (AAPS PharmSciTech, 2024)

Late Quaternary deformation, strain partitioning, and fold-thrust belt widening in the Eastern Himalayan Syntaxis, India - Ishwar Singh; R. Jayangondaperumal; Arjun Pandey; Rao Singh Priyanka; Rajeeb Lochan Mishra; P. Morthekai; Shraddha Jagtap; Pradeep Srivastava; Pankaj Kumar; Sundeep Chopra (Tectonophysics, 2024)

Meta-QTL analysis in wheat: progress, challenges and opportunities - Divya Sharma; Anita Kumari; Priya Sharma; Anupma Singh; Anshu Sharma; Zahoor Ahmad Mir; Uttam Kumar; Sofora Jan; M. Parthiban; Reyazul Rouf Mir; Pradeep Bhati; Anjan Kumar Pradhan; et al. (Theoretical and Applied Genetics, 2023)

Evaluation of indigenous accessions of wheat for spot blotch resistance at the seedling and adult plant stage - Yaratha Nishith Reddy; Malkhan Singh Gurjar; Tej Pratap Jitendra Kumar; Mahender Singh Saharan; Sundeep Kumar; Mukesh Kumar Khokhar; Naresh Kumar; Rashmi Aggarwal (Indian Phytopathology, 2023)

Characterization of stress-induced changes in morphological, physiological and biochemical properties of Indian bread wheat (Triticum aestivum L.) under deficit irrigation - Deepali Upadhyay; Neeraj Budhlakoti; D. C. Mishra; Jyoti Kumari; Vijay Gahlaut; Nidhee Chaudhary; Jasdeep Chatrath Padaria; Sindhu Sareen; Sundeep Kumar (Genetic Resources and Crop Evolution, 2023)

Polyaniline doped silk fibroin-PCL Electrospunfiber: An electroactive fibrous sheet for full-thickness wound healing study - Ragavi Rajasekaran; Atul Kumar Ojha; Venkata Sundeep Seesala; Arman Kunwar Hansda; Nantu Dogra; Jhansi Lakshmi Parimi; Sabyasachi Roy; Ritobrata Goswami; Mamoni Banerjee; Santanu Dhara (Chemical Engineering Journal, 2023)

Molecular aspects of ABCB1 and ABCG2 in Gallbladder cancer and its clinical relevance - Nimisha; Sundeep Singh Saluja; Abhay Kumar Sharma; Phani Kumar Nekarakanti; Apurva; Arun Kumar; Real Sumayya Abdul Sattar; Hasib Anjum; Vineeta Vijay Batra; Syed Akhtar Husain (Molecular and Cellular Biochemistry, 2023)

Clinical significance of SPOP and APC gene alterations in colorectal cancer in Indian population - Asgar Ali; Nimisha; Abhay Kumar Sharma; Pramod Kumar Mishra; Sundeep Singh Saluja (Molecular Genetics and Genomics, 2023)

Exploration of Hemicellulosic Hydrolysates Derived from Arundo Donax and Cynodon Dactylon as Potential Substrates for Microbial Protein Production by Candida Tropicalis - Arushdeep Sidana; Payal Guleria; Sundeep Kaur; Sudesh Kumar Yadav (BioEnergy Research, 2023)

Formulation Intervention to Overcome Decreased Kinetic Solubility of a Low Tg Amorphous Drug - Mangesh S. Bordawekar; Madhu Pudipeddi; Colleen E. Ruegger; Sundeep S. Dhareshwar (AAPS PharmSciTech, 2023)

Mapping cellular senescence networks in human diabetic foot ulcers - Grace T. Yu; Dileep D. Monie; Sundeep Khosla; Tamar Tchkonia; James L. Kirkland; Saranya P. Wyles (GeroScience, 2023)

Comparative transcriptome profiling of near isogenic lines PBW343 and FLW29 to unravel defense related genes and pathways contributing to stripe rust resistance in wheat - Zahoor Ahmad Mir; Divya Chauhan; Anjan Kumar Pradhan; Vivek Srivastava; Divya Sharma; Neeraj Budhlakoti; Dwijesh Chandra Mishra; Vasudha Jadon; Tanmaya Kumar Sahu; Monendra Grover; Om Prakash Gangwar; Subodh Kumar; et al. (Functional & Integrative Genomics, 2023)

GWAS scans of cereal cyst nematode (Heterodera avenae) resistance in Indian wheat germplasm - Vikas Kumar Singh; Deepti Chaturvedi; Saksham Pundir; Deepak Kumar; Rajiv Sharma; Sundeep Kumar; Shiveta Sharma; Shailendra Sharma (Molecular Genetics and Genomics, 2023)

Recent advances on genome-wide association studies (GWAS) and genomic selection (GS); prospects for Fusarium head blight research in Durum wheat - Zahoor Ahmad Mir; Tilak Chandra; Anurag Saharan; Neeraj Budhlakoti; D. C. Mishra; M. S. Saharan; Reyazul Rouf Mir; Amit Kumar Singh; Soumya Sharma; V. K. Vikas; Sundeep Kumar (Molecular Biology Reports, 2023)

Evaluation of differentially expressed genic marker linked resistance gene analog (RGAs) effective at seedling stage against spot blotch in wheat - Aakash Yadav; Tilak Chandra; Sundeep Kumar (Cereal Research Communications, 2023)

Establishing the Safe Space via Physiologically Based Biopharmaceutics Modeling. Case Study: Fevipiprant/QAW039 - Alexandros Kourentas; Monika Gajewska; Wen Lin; Sundeep S. Dhareshwar; Caroline Steib-Lauer; Swarupa Kulkarni; Stefan Hirsch; Tycho Heimbach; Martin Mueller-Zsigmondy (The AAPS Journal, 2023)

Spatial distribution of fossil fuel derived CO2 over India using radiocarbon measurements in crop plants - Rajveer Sharma; Ravi Kumar Kunchala; Sunil Ojha; Pankaj Kumar; Satinath Gargari; Sundeep Chopra (Journal of Environmental Sciences, 2023)

Oral Delivery of Nucleic Acid Therapies for Local and Systemic Action - Neha Kumari; Kasturi Siddhanta; Sudipta Panja; Vineet Joshi; Chinmay Jogdeo; Ekta Kapoor; Rubayat Khan; Sai Sundeep Kollala; Balawant Kumar; Diptesh Sil; Amar B. Singh; Daryl J. Murry; et al. (Pharmaceutical Research, 2023)

Landraces-potential treasure for sustainable wheat improvement - Sneha Adhikari; Jyoti Kumari; Sherry Rachel Jacob; Pramod Prasad; O. P. Gangwar; Charu Lata; Rajnikant Thakur; Amit Kumar Singh; Ruchi Bansal; Sundeep Kumar; S. C. Bhardwaj; Subodh Kumar (Genetic Resources and Crop Evolution, 2022)

Computational Assessment of Valvular Dysfunction in Discrete Subaortic Stenosis: A Parametric Study - Jason A. Shar; Sundeep G. Keswani; K. Jane Grande-Allen; Philippe Sucosky (Cardiovascular Engineering and Technology, 2021)

Disruptions in oral and nasal microbiota in biomass and tobacco smoke associated chronic obstructive pulmonary disease - Dhiraj M. Agarwal; Dhiraj P. Dhotre; Shreyas V. Kumbhare; Akshay H. Gaike; Bill B. Brashier; Yogesh S. Shouche; Sanjay K. Juvekar; Sundeep S. Salvi (Archives of Microbiology, 2021)

Effectiveness of a Patient Education Class to Enhance Knowledge about Lung Cancer Screening: a Quality Improvement Evaluation - Lori C. Sakoda; Melanie A. Meyer; Neetu Chawla; Michael A. Sanchez; Maruta A. Blatchins; Sundeep Nayak; Karen San; Gary K. Zin; George Minowada (Journal of Cancer Education, 2020)

Microsatellite analysis reveals low interpopulation differentiation in velvet bean (Mucuna pruriens var. utilis) of India - Pittala Ranjith Kumar; Sai Sundeep; N. Sathyanarayana (The Nucleus, 2020)

Molecular genetic diversity analysis for heat tolerance of indigenous and exotic wheat genotypes - Sindhu Sareen; Nabin Bhusal; Manoj Kumar; Pradeep Kumar Bhati; Renu Munjal; Jyoti Kumari; Sundeep Kumar; A. K. Sarial (Journal of Plant Biochemistry and Biotechnology, 2020)

Cyclodextrin-based delivery systems for dietary pharmaceuticals - Divya Arora; Ankit Saneja; Sundeep Jaglan (Environmental Chemistry Letters, 2019)

Regional Differentiation of Adipose-Derived Stem Cells Proves the Role of Constant Electric Potential in Enhancing Bone Healing - Sindhuja D. Eswaramoorthy; Sundeep Bethapudi; Shahdab I. Almelkar; Subha N. Rath (Journal of Medical and Biological Engineering, 2018)

Therapeutic applications of resveratrol nanoformulations - Divya Arora; Sundeep Jaglan (Environmental Chemistry Letters, 2018)

Modern pollen rain from Udhampur (Jammu and Kashmir), India: insights into pollen production, dispersal, transport and preservation - M.F. Quamar; S. Nawaz Ali; Sundeep K. Pandita; Yudhbir Singh (Palynology, 2018)

Air pollution and respiratory health among diabetic and non-diabetic subjects in Pune, India—results from the Wellcome Trust Genetic Study - Morteza Abdullatif Khafaie; Sundeep Santosh Salvi; Chittaranjan Sakerlal Yajnik; Ajay Ojha; Behzad Khafaie; Sharad Damodar Gore (Environmental Science and Pollution Research, 2017)

Statistical Parametric Mapping of HR-pQCT Images: A Tool for Population-Based Local Comparisons of Micro-Scale Bone Features - Julio Carballido-Gamio; Serena Bonaretti; Galateia J. Kazakia; Sundeep Khosla; Sharmila Majumdar; Thomas F. Lang; Andrew J. Burghardt (Annals of Biomedical Engineering, 2017)

Synthesis of some novel oxazolidinone-thiazole hybrids as potential antimicrobial, antioxidant and UV mediated DNA damage protecting agents - Kamalneet Kaur; Vinod Kumar; Vikas Beniwal; Vikas Kumar; Neeraj Kumar; Vishal Sharma; Sundeep Jaglan (Medicinal Chemistry Research, 2016)

De novo transcriptome sequencing facilitates genomic resource generation in Tinospora cordifolia - Rakesh Singh; Rajesh Kumar; Ajay Kumar Mahato; Ritu Paliwal; Amit Kumar Singh; Sundeep Kumar; Soma S. Marla; Ashok Kumar; Nagendra K. Singh (Functional & Integrative Genomics, 2016)

Synthesis and characterization of novel conjugates of 4-[3-(aryl/heteroaryl)-3-oxo-propenyl]-benzaldehyde with thiazole and thiazolidinones as possible voltage-gated sodium channel blockers - Sundeep Pandey; Pankaj K. Sonar; Shailendra K. Saraf (Medicinal Chemistry Research, 2016)

Erratum to: Identification of invasion proteins of Cryptosporidium parvum - Preeti Singh; Bijay Ranjan Mirdha; Alagiri Srinivasan; Lokesh A. Rukmangadachar; Sundeep Singh; Pratibha Sharma; Gururao Hariprasad; Kalpana Luthra (World Journal of Microbiology and Biotechnology, 2016)

Identification of invasion proteins of Cryptosporidium parvum - Preeti Singh; Bijay Ranjan Mirdha; Alagiri Srinivasan; Lokesh A. Rukmangadachar; Sundeep Singh; Pratibha Sharma; Hariprasad Gururao; Kalpana Luthra (World Journal of Microbiology and Biotechnology, 2015)

Novel (E)-1-aryl-2-(3,5-dimethyl-4-(aryldiazenyl)-1H-pyrazol-1-yl)ethanones: solvent-free synthesis and antimicrobial, antioxidant and UV-mediated DNA damage protective activity studies - Kamalneet Kaur; Vinod Kumar; Vikas Beniwal; Vikas Kumar; K. R. Aneja; Vishal Sharma; Sundeep Jaglan (Medicinal Chemistry Research, 2015)

Solvent-free synthesis of novel (E)-2-(3,5-dimethyl-4-(aryldiazenyl)-1H-pyrazol-1-yl)-4-arylthiazoles: determination of their biological activity - Kamalneet Kaur; Vinod Kumar; Vikas Beniwal; Vikas Kumar; K. R. Aneja; Vishal Sharma; Sundeep Jaglan (Medicinal Chemistry Research, 2015)

A report of rifampin-resistant leprosy from northern and eastern India: identification and in silico analysis of molecular interactions - Sundeep Chaitanya Vedithi; Mallika Lavania; Manoj Kumar; Punit Kaur; Ravindra P. Turankar; Itu Singh; Astha Nigam; Utpal Sengupta (Medical Microbiology and Immunology, 2015)

One-pot synthesis and cytotoxic evaluation of amide-linked 1,4-disubstituted 1,2,3-bistriazoles - Kashmiri Lal; C. P. Kaushik; Krishan Kumar; Ashwani Kumar; Asif Khurshid Qazi; Abid Hamid; Sundeep Jaglan (Medicinal Chemistry Research, 2014)

CAAT box- derived polymorphism (CBDP): a novel promoter -targeted molecular marker for plants - Amit Kumar Singh; M K Rana; Sonika Singh; Sundeep Kumar; Rajesh Kumar; Rakesh Singh (Journal of Plant Biochemistry and Biotechnology, 2014)

Stem and leaf rust resistance in wild relatives of wheat with D genome (Aegilops spp.) - V. K. Vikas; M. Sivasamy; J. Kumar; P. Jayaprakash; Sundeep Kumar; R. Parimalan; Arun Kumar; Kalyani Srinivasan; J. Radhamani; Sherry Rachel Jacob; Mamata Yadav; Jyotisna Rani; et al. (Genetic Resources and Crop Evolution, 2014)

Long nonoding RNAs in the X-inactivation center - Emily Maclary; Michael Hinten; Clair Harris; Sundeep Kalantry (Chromosome Research, 2013)

Molecular approaches for designing heat tolerant wheat - Sundeep Kumar; Prerna Kumari; Uttam Kumar; Monendra Grover; Amit Kumar Singh; Rakesh Singh; R. S. Sengar (Journal of Plant Biochemistry and Biotechnology, 2013)

Loop-mediated isothermal amplification (LAMP) assay for rapid detection of Entamoeba histolytica in amoebic liver abscess - Preeti Singh; Bijay Ranjan Mirdha; Vineet Ahuja; Sundeep Singh (World Journal of Microbiology and Biotechnology, 2013)

Genomic characterization of drought tolerance-related traits in spring wheat - Sundeep Kumar; Sunish Kumar Sehgal; Uttam Kumar; P. V. Vara Prasad; Arun Kumar Joshi; Bikram Singh Gill (Euphytica, 2012)

Robust QCT/FEA Models of Proximal Femur Stiffness and Fracture Load During a Sideways Fall on the Hip - Dan Dragomir-Daescu; Jorn Op Den Buijs; Sean McEligot; Yifei Dai; Rachel C. Entwistle; Christina Salas; L. Joseph Melton; Kevin E. Bennet; Sundeep Khosla; Shreyasee Amin (Annals of Biomedical Engineering, 2011)

Identification of QTLs for stay green trait in wheat (Triticum aestivum L.) in the ‘Chirya 3’ × ‘Sonalika’ population - Uttam Kumar; Arun K. Joshi; Maya Kumari; Rajneesh Paliwal; Sundeep Kumar; Marion S. Röder (Euphytica, 2010)

Mapping of resistance to spot blotch disease caused by Bipolaris sorokiniana in spring wheat - Uttam Kumar; Arun K. Joshi; Sundeep Kumar; Ramesh Chand; Marion S. Röder (Theoretical and Applied Genetics, 2009)

Investigation of Solubility and Dissolution of a Free Base and Two Different Salt Forms as a Function of pH - Shoufeng Li; SuiMing Wong; Sundeep Sethia; Hassan Almoazen; Yatindra M. Joshi; Abu T. M. Serajuddin (Pharmaceutical Research, 2005)

Antitubercular activity of garlic (allium sativum) extract on combination with conventional antitubercular drugs in tubercular lymphadenitis - R. L. Gupta; Sundeep Jain; V. Talwar; H. C. Gupta; P. S. Murthy (Indian Journal of Clinical Biochemistry, 1999)

Studies on a new antitubercular drug, trifluoperazine: Its effect in combination with conventional antitubercular drugs in tubercular lymphadenitis - R. L. Gupta; Sundeep Jain; V. Talwar; H. C. Gupta; P. S. Murthy (Indian Journal of Clinical Biochemistry, 1998)